(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Discourse functions as a medium through which a particular act of communication is carried out. In this process, communicative intentions are often expressed through a variety of linguistic and non-linguistic means, many of which are professionally oriented. The adequacy of the interlocutors’ speech behavior serves as an indicator of whether the discourse interaction is successful or unsuccessful and, consequently, whether the communicative goal is achieved or not. In this context, discursive competence plays a crucial role. It encompasses communicative competence and involves mastery of specific domains, situations, and topics of interaction, as well as familiarity with professionally oriented texts, country-specific and socio-cultural knowledge relevant to different languages. Such competence manifests itself in effective verbal communication, along with communicative and intellectual skills adapted to the professional communication environment.